Reviews and Protocols in DT40 Research Subcellular Biochemistry - Buerstedde, Jean-Marie.; Takeda, Shunichi; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Research is fast paced and advances in RNA interference have recently opened up new opportunities for genetic experiments in human cell lines. However, the possibility to easily modify the genome still remains a powerful tool to investigate the function of coding and regulatory sequences in the vertebrate genome. DT40 has never been a quick and easy road to fame. It would be unfair to blame this on DT40 as it has proven to be a reliable and robust companion with fast doubling time, easy clonability and a relatively stable karyotype. If this model system is going to flourish over the next 15 years, it will be thanks to ingenious and original researchers. They may feel as if they work outside the mainstream, but they can take heart by the fact that only the clever exploitation of diversity and conservation makes biological research both elegant and rewarding. It is with this in mind that the DT40 handbook has been conceived and written. This book provides an up to date overview of the different facets of research, and also intends to help newcomers get started and avoid looming pitfalls. The collection of protocols which have been kindly provided by a number of laboratories will be particularly useful in this regard.
DT40 gene disruptions: a how-to for the design and the construction of targeting vectors -- Immunoglobulin gene conversion or hypermutation: that's the question -- Genome resources for the DT40 community -- Chromosome engineering in DT40 cells and mammalian centromere function -- Function of RECQ family helicase in genome stability -- Genetic analysis of apoptotic execution -- The DT40 system as a tool for analyzing kinetochore assembly -- Analysing the DNA damage and replication checkpoints in DT40 cells -- Using DT40 to study clathrin function -- Genetic analysis of B cell signaling -- DT40 mutants: a model to study transcriptional regulation of B cell development and function -- Transcription and RNA processing factors play complex roles in DT40 cells -- Participation of histones, histone modifying enzymes and histone chaperonesin vertebrate cell functions -- Analysis of gene expression, copy number and palindrome formation with a DT40 enriched CDNA microarray -- Calcium signaling, ion channels and more -- Analysis of DNA replication damage bypass and its role in immunoglobulin repertoire development -- The fanconi anemia pathway promotes homologous recombination repair in DT40 cell line -- Phenotypic analysis of cellular responses to DNA damage -- ATM, a paradigm for a stress-responsive signal transducer in higher vertebrate cells -- Stable non-targeted transfection of DT40 -- Basic cell culture conditions -- Excision of floxed-DNA sequences by transient induction of MER-CRE-MER -- Immunoglobulin gene conversion and hypermutation assay by facs -- Target screening by PCR -- Mitotic index determination by flow cytometry -- Centrifugal elutriation as a means of cell cycle phase separation and synchronisation -- Preparation of genomic DNA for microarray-based comparative genome hybridization -- Analysis of cellular Mg2+ in DT40 cells -- Transient transfection of DT40 -- Retroviral transduction of DT40 -- Colony survival assay -- Subcloning DT40 by limiting dilution -- Subnuclear immunofluorescence -- Sister chromatid exchange assay -- 2D cell cycle analysis -- Purification of tap-tagged proteins by two-step pull down from DT40 cells -- Synchronization of cells -- Targeted transfection of DT40 cells -- Luciferase reporter assay -- Indirect immunofluorescence microscopy -- Quantification of receptor-mediated endocytosis -- Measurement of DNA synthesis and strand breaks using alkaline sucrose density gradient centrifugation -- Isolation of nuclear and cytoplasmic proteins from DT40 cell lines.
Keywords: Life sciences; Cancer research; Biochemistry; Cell biology; Vertebrates; Life Sciences; Cell Biology; Cancer Research; Biochemistry, general; Life Sciences, general; Vertebrates; Electronic books